The Effect of Content Creator Attributes on Purchase Intention in Live Commerce: The Mediating Roles of Perceived Authenticity and Parasocial Interaction - Sanny, Annisa; Yanti, Eli Delvi; Muda, Iskandar (Pascasarjana STIE Amkop Makassar, 2025)
Live commerce is increasingly widespread in Indonesia, yet the psychological mechanisms that convert viewers into buyers remain underexplored. This study examines how content creator attributes expertise, trustworthiness, attractiveness, brand–creator fit, and responsiveness—affect purchase intention through the serial mediation of perceived authenticity and parasocial interaction. A survey was conducted among live-commerce users in Medan with sampling 278 respondent using purposive sampling. Data were analyzed using two-stage PLS-SEM with bootstrap. The measurement model met reliability and validity thresholds loadings 0.77–0.86; α and CR ≥ 0.80; AVE ≥ 0.50; HTMT < 0.85. Results show that content creator attributes significantly influence perceived authenticity β = 0.583; p < 0.001; perceived authenticity influences parasocial interaction β = 0.517; p < 0.001; and parasocial interaction influences purchase intention β = 0.468; p < 0.001. There is also a significant indirect effect of content creator attributes on purchase intention through perceived authenticity and parasocial interaction β = 0.141; p < 0.001. Explanatory power is moderate R² authenticity = 0.34; R² parasocial = 0.27; R² purchase intention = 0.22; all Q² > 0. The findings formalize a mechanism in which authenticity fosters closeness and, in turn, raises purchase intention, offering actionable guidance for curating creators and designing responsive, transparent live sessions